Non-Financial Variables Determining Performance Village Credit Institutions - Wiagustini, Ni Luh Putu; Wistawan, I Made Andika Pradnyana (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 2 Tahun 2021, 2021)
The Village Credit Institution (LPD) as a rural microfinance institution, its operational activities are limited within the village area, experienced a fairly rapid development from eight units in 1984, reaching 1443 units in 2019, but there were 177 units (12.35 percent) not operating. The measurement of the performance of LPD is determined from the indicators of the level of health which are more assessed from financial ratios. In this study, non-financial variables were examined as variables that affect financial performance. This study aims to analyze the non-financial variables that determine the performance of LPD, which in this study are market orientation, entrepreneurial orientation, financial literacy, financial inclusion. The research population is LPD operating in Bali Province in 2019 as many as 1256 units. determined using the Slovin formula with an allowance of 10 percent, which is 93 units, Sampling with stratified proportional random sampling based on the health level of LPD, The method of analysis is Partial Least Square (PLS), it was found that the increase in entrepreneurial orientation, market orientation, financial literacy and the financial inclusion of the Village Credit Institution management has an impact on improving its performance. The implications for the management of the Village Credit Institution in improving its performance can increase entrepreneurial orientation, market orientation. financial literacy, management inclusion.